EXPLORATION OF OBSTACLES FACED BY SUCCESSORS IN THE INTERGENERATIONAL TRANSITION PROCESS OF FAMILY BUSINESS - Fuad, Muhammad; Sudarma, Made; Irianto, Gugus (Jurnal Aplikasi Manajemen, 2019)
One crucial step that must be faced by a family company in maintaining the sustainability of its business is the intergenerational transition process from a predecessor to successors. This study aims to explore the obstacles faced by successors in undergoing the intergenerational transition process of their family business. The study was conducted on small and medium-sized family business in Kota Batu region undergoing the process. Nine successors were chosen purposively as the key informants using a snowball sampling technique. Data collected through in-depth interview, then the researcher reflects it through narrative analysis approach. Based on the results of interpretation identified that three major obstacles faced by successors while undergoing the intergenerational transition process of their family business. To overcome these obstacles, it takes intense communication between the successors and predecessor, as well as among the successors themselves, while undergoing the process.